2014
DOI: 10.1248/bpb.b14-00193
|View full text |Cite
|
Sign up to set email alerts
|

Total Flavonoids of Litsea Coreana Enhance the Cytotoxicity of Oxaliplatin by Increasing Gap Junction Intercellular Communication

Abstract: Oxaliplatin is widely used in the treatment of variety of cancers, including cancer of the testis and colorectum. Gap junctions (GJs) can amplify the cytotoxicity of antinoeoplastic drugs through the bystander effect in different cancer cells. In this study, we demonstrate that total flavonoids of litsea coreana (TFLC), one extract from the dried leaves of litsea coreana leve, increase the cytotoxicity of oxaliplatin in mouse testicular cancer I-10 cells. We found that cell survival was substantially decreased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 29 publications
0
13
0
1
Order By: Relevance
“…Upregulating connexin expression can increase the sensitivity of many cancers 29, 30 to chemotherapy drugs including Taxol 31 . Connexin 43 (Cx43) is the most widely expressed in different tissues among the group of connexins 32 .…”
Section: Resultsmentioning
confidence: 99%
“…Upregulating connexin expression can increase the sensitivity of many cancers 29, 30 to chemotherapy drugs including Taxol 31 . Connexin 43 (Cx43) is the most widely expressed in different tissues among the group of connexins 32 .…”
Section: Resultsmentioning
confidence: 99%
“…Numerous studies have revealed the significant role of GJs in tumors, since recovered expression of connexin that forms GJs or recovered function of GJs could reduce the cell malignant phenotype (11,34,35). The expression of connexin and its derived homotypic GJ suppressed the invasion of tumor cells (36,37).…”
Section: A B Discussionmentioning
confidence: 99%
“…In contrast, to enhance the function of gap junctions, we treated the cells with 10 μmol/L RA (Sigma) or 10 μmol/L galangin (China Pharmaceutical Biological Products Inspection Institute, Beijing, China) for 24 hours . Galangin is a flavonoid compound that enhances gap junction function, increasing the cytotoxicity of the antitumor drugs cisplatin and oxaliplatin …”
Section: Methodsmentioning
confidence: 99%
“…24 Galangin is a flavonoid compound that enhances gap junction function, increasing the cytotoxicity of the antitumor drugs cisplatin and oxaliplatin. 25,26…”
Section: Drug Treatment Of Gap Junctionsmentioning
confidence: 99%